FRI0411 A Multicenter Prospective Evaluation of the Risk Profile in Pregnant Patients with Persistent Positivity for Antiphospholipid Antibodies (APL). (9th June 2015) - Fredi, M.; Aggogeri, E.; Bettiga, E.; Andreoli, L.; Lazzaroni, M.G.; Le Guern, V.; Lojacono, A.; Morel, N.; Nalli, C.; Taraborelli, M.; Zatti, S.; Piette, J.C.; et al.
Abstract : Background: Antiphospholipd antibodies positivity (aPL) are considered as risk factors for a poor obstetric outcome. Several clinical and laboratory features have been associated with the risk of a pregnancy failure. Objectives: To determine risk factors of having poor pregnancy outcome in patients (pts) with established aPL positivity with or without a diagnosis of primary antiphospholipid syndrome (APS) despite the administration of the accepted "conventional treatment" (low dose aspirin (LDA) and heparin (H)) when indicated. Methods: We considered 276 pregnancies in 193 women prospectively followed in the 3 Institutions involved between 2000 and 2014. None of the pts had a concomitant systemic autoimmune disease. Data were collected from clinical charts using a common database and included the 3 assays to detect aPL. We considered as "poor pregnancy outcome" the occurrence of a pregnancy loss (early miscarriages and fetal loss), perinatal deaths, preterm deliveries before the 34 weeks and HELLP Syndrome. Results: Among the 193 pts, 127 fulfilled the classification criteria for APS and 66 did not. According to their clinical history and/or the laboratory, the patients were divided in 4 groups: 87 pts with pure obstetric APS (O-PAPS, 121 pregnancies), 40 thrombotic with or without obstetric APS (T-PAPS, 66 pregnancies), 32 incomplete APS (incomplete clinical or laboratory criteria, 47 pregnancies) and 34 aPL carriers without any clinical manifestation prior to the index pregnancy (42 pregnancies). The mean age at the pregnancy onset was 32.5 years (SD 5.09), the global rate of live births was 86.9%; poor obstetrical outcome was observed in 48 pregnancies (17.4%); the outcome in the groups is detailed in table 1 . In the table 2 we reported the several features that resulted, at the univariate analysis, with a significant prevalence among the pts with poor obstetric outcome regardless of the group. A thrombotic event occurred in 5 pts: 2 during pregnancies (1 O-APS and 1 aPL carrier) and 3 during puerperium, with 2 deep venous thrombosis with pulmonary embolism in 1 O-APS and 1 T-APS and 1 myocardial infarction after an early miscarriage in a T-APS. Finally 1 T-APS had a catastrophic syndrome during puerperium, and 3 pts (2 T-APS and 1 aPL carrier) had an onset or a relapse of mild-moderate thrombocytopenia (without HELLP syndrome). The combination of LDA plus H was administered in 94% of pregnancies that fulfilled the criteria for APS, while the rate was 57% for the incomplete APS and 39% for aPL carriers. Conclusions: Our preliminary results show that, regardless of a high rate of use of the conventional therapy, a poor obstetrical outcome and the occurrence of several severe maternal complications were not uncommon, especially in T-PAPS and aPL carriers. Several factors (irrespectively of the diagnosis) seem to be associated with serological, clinical and acquired features. Disclosure of Interest: None declared